Efficient time reversal strategy for MISO-OFDM systems - Issam Maaz; Samer Alabed (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
In this work, we are interested in implementing, developing, and evaluating a time reversal strategy for a multiple-input single-output orthogonal frequency division multiplexing system. This strategy enjoys a good trade-off between the computational complexity and performance in terms of bit error rate where it offers a good coding gain by forming a beam in the direction of the destination at a price of channel state information available at the transmitter. In time reversal technique, a higher coding and diversity gain can be achieved by increasing the number of transmitting antennas, which focuses the formed beam to the direction of the destination antenna. By achieving this, the received signal-to-noise ratio can be maximized which makes time reversal a good candidate for multiple-input single-output systems while keeping a low complexity. The performance of the proposed system is evaluated in terms of bit error rate where our simulations show that the proposed strategy enjoys the full diversity gain, which is equal to the number of transmitting antennas. Moreover, a robust channel estimation technique is proposed to improve the overall system in terms of bit error rate.